CCR3 induced-p42/44 MAPK activation protects against staurosporine induced-DNA fragmentation but not apoptosis in airway smooth muscle cells - Markwick, L. J.; Clements, D.; Roberts, M. E.; Ceresa, C. C.; Knox, A. J.; Johnson, S. R. (Clinical and experimental allergy, 2012)
Summary Background Chemokine receptors (CCRs) are expressed on airway smooth muscle (ASM) cells. As their ligands are present in the airways in asthma, we hypothesized that ASM CCR activation could promote the increase in ASM mass seen in patients with chronic asthma. Objective To determine which CCRs are expressed by ASM cells and their potential functional relevance to the chronic airway changes seen in asthma. Methods CCR expression in primary ASM cell cultures and airway biopsies from patients with and without asthma was examined by RT‐PCR, fluorescence‐activated cell sorting and immunohistochemistry. ASM p42/44 MAPK activity, proliferation, migration and apoptosis were examined by western blotting, thymidine incorporation, transwell assay and TUNEL assay respectively. Results CCR3 was the most frequently expressed CCR protein and was present on 79 ± 14% of cells. CX3CR1 and CXCR6 were present on 6% and 11% of cells respectively. CCR3 ligands CCL11 and CCL24 caused rapid activation of p42/44 MAPK but not Akt. CCR3 activation did not affect ASM proliferation, migration or VEGF secretion. DNA fragmentation detected by TUNEL staining could be induced by staurosporine and Fas activation although only Fas activation resulted in caspase 3 cleavage. CCL11 and CCL24 protected ASM cells against DNA fragmentation dependent upon p42/44 MAPK activity only via caspase 3 independent pathways. CCR3 was expressed in the smooth muscle and epithelium in the airways of patients with and without asthma. Smooth muscle cell DNA fragmentation in the airways of patients with stable asthma and controls was very uncommon. Conclusions and Clinical Relevance CCR3 is strongly expressed by ASM cells in vitro and in vivo. Protection against cell death by CCR3 activation is dependent on p42/44 MAPK but does not affect caspase 3 mediated apoptosis.